Private Rights to Public Property: The Evolution of Common Property in Canada - Hamill, Sarah (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
This article uses the recent Occupy litigation of Batty v. City of Toronto to argue that Canadian courts no longer have a robust understanding of common property and its attendant rights. The lack of judicial understanding of common property is hardly surprising given property theory’s focus on private property, particularly individual private property. This article argues that rather than use the traditional analogy of governments holding common property in trust for the public, Batty relies on an analogy of common property which treats the government as an owner. The emergence of the latter understanding of common property can be traced to Supreme Court jurisprudence from the early 1990s. Although the government-as-owner analogy of common property was introduced in a concurring judgment, more recent Supreme Court decisions have since reiterated the analogy. Such an understanding of common property is a clear attempt to force all property into a private property model and emphasize the rights of owners above all other rights in property. This article argues that the government-as-owner analogy is problematic given its emphasis on the government’s use of property rather than the public’s benefit from common property and calls for a return to the trust analogy of common property.